Prescribing pattern of antimicrobials in various clinical departments of a tertiary care hospital - V., Rohith; H., Manjunatha C.; N., Anusha; J., Jayasheela; Topno, Isabella (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Antimicrobials are one of the most commonly used group of drugs. Their overuse and inappropriate use is one of the major concerns today. Assessment of prescribing pattern of antimicrobials provides insight into the health consequences and helps update antimicrobial usage guidelines. Hence this study was conducted with an objective to analyse the prescribing pattern of the antimicrobials. Methods: A cross sectional study was conducted based on the prescriptions collected from Department of Pharmacy, Pondicherry Institute of Medical Sciences (PIMS), Puducherry. A total of 838 outpatient prescriptions were collected from four clinical departments, viz. General Medicine, General Surgery, Pediatrics and Obstetrics & Gynecology for a period of four months. The data collected were analysed using descriptive statistics. Results: Among 838 prescriptions 188 (22.43%) contained antimicrobials. Among the various departments, number of prescriptions with antimicrobials were more in department of General surgery (34.42 %) followed by Obstetrics & Gynecology (24.77 %). The commonly prescribed antibiotics were penicillins (25.47%), fluoroquinolones (12.73%), cephalosporins (10.84%), macrolides (8.96%), nitroimidazoles (6.60%) and tetracyclines (4.71%). Among the total antimicrobials, percentage of drugs prescribed by generic name and from National list of essential medicines (NLEM) were 38.20% and 80.18% respectively. Majority of antimicrobials (58.01%) were prescribed as oral tablets/ capsules. Conclusions: It was found that penicillins were the most commonly prescribed group of antimicrobials, significantly less number of antimicrobials were prescribed by generic name, 80.18% of antimicrobials were prescribed from NLEM and tablets/ capsules were the most common dosage forms.